Benefits of non-drug interventions for people with suicidal crises in unipolar depression. (13th November 2019) - Berger, E; Fuchs, S; Baier, N; Peters, H; Busse, R
Abstract: Background: Depression is one of the most common and serious diseases worldwide: According to WHO, more than 300 million people worldwide were affected by depression in 2015. In this group, the suicide rate is about 20 times higher than the population average. In Germany, around 10, 000 people take their lives each year, many of them suffering from depression. The Institute for Quality and Efficiency in Health Care commissioned the Department of Health Care Management at the Berlin University of Technology to conduct a Health Technology Assessment on whether non-drug interventions influence coping with suicidal crises in unipolar depression. Methods: A systematic search of primary studies and systematic reviews (e.g., in MEDLINE, PSYCINFO) was performed to assess the benefit of ambulatory crisis intervention programmes or psychosocial interventions compared to another non-drug treatment, drug treatment, inpatient treatment or no treatment/waiting list in adult suicidal patients with unipolar depression regarding patient-relevant outcomes (e.g., suicide attempts, suicidal ideation, depression). Results: The search yielded a total of 4, 159 hits. After two rounds of screening for relevance and removing duplicates, 4 studies remained for inclusion in the qualitative and quantitative analysis. The studies present RCTs assessing the effects of cognitive behavioural therapy (CBT) of the 2. and 3. wave - all short-term programmes focussing on suicidality. Results indicate a benefit of CBT compared to standard treatment, depending on the outcome, on the "wave" and on the time of follow up assessment. Conclusions: There is some evidence on benefits of CBT for adult patients with suicidal crises in unipolar depression. However, the quality of the included RCTs is weak and evidence on benefits of other non-drug interventions in outpatient care is missing. Further research is needed to identify effective interventions, especially for the vulnerable weeks immediately after suicide attempt. Key messages: Short term cognitive behavioural therapy with suicidal prevention elements may influence coping with suicidal crises in unipolar depression positively. Further research is needed to identify effective interventions for the vulnerable weeks immediately after suicide attempt.